1977
DOI: 10.1159/000231820
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Immune Response in Neonatal Piglets by Maternal Antibody

Abstract: The ability of maternal antibody to regulate the humoral immune response to sheep erythrocytes and the hapten-carrier conjugate trinitrophenylated sheep erythrocytes (TNP-SRBC) was investigated in neonatal piglets. It was found that in this system, passively acquired maternal antibody would completely inhibit the in vitro primary immune response to SRBC while leaving the response the TNP intact. Data suggest that maternal antibody is regulating the in vitro response at the B-cell level since T-cell helper func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The suppression of IgE responsiveness is noteworthy (Bednar-Tantscher et al, 2001;Jarret and Hall, 1979;Roberts and Turner, 1983), which might explain the delayed onset of atopy among breastfed infants (Halpern et al, 1973). Suppression in newborn artiodactyls has also been shown (Hammerberg et al, 1989;Hoerlein, 1957;Husband and Lascelles, 1975;Klobasa et al, 1981Klobasa et al, , 1986Logan et al, 1974;Muscoplat et al, 1977). In piglets reared in an autosow, ingestion of 3.5 g purified IgG suppresses de novo synthesis of IgG and IgA to the same extent as colostrum .…”
Section: Immunomodulation By Passive Igs and Antibodiesmentioning
confidence: 99%
“…The suppression of IgE responsiveness is noteworthy (Bednar-Tantscher et al, 2001;Jarret and Hall, 1979;Roberts and Turner, 1983), which might explain the delayed onset of atopy among breastfed infants (Halpern et al, 1973). Suppression in newborn artiodactyls has also been shown (Hammerberg et al, 1989;Hoerlein, 1957;Husband and Lascelles, 1975;Klobasa et al, 1981Klobasa et al, , 1986Logan et al, 1974;Muscoplat et al, 1977). In piglets reared in an autosow, ingestion of 3.5 g purified IgG suppresses de novo synthesis of IgG and IgA to the same extent as colostrum .…”
Section: Immunomodulation By Passive Igs and Antibodiesmentioning
confidence: 99%
“…Maternal antibodies do not only confer passive protection, but may in addition influence the developing immune system of the newborn in such a way that antigen‐induced immune responses may seemingly be suppressed or can be enhanced. Since the 1940s until present, it has been reported that antibody responses at an early age in the offspring of immunized mothers are suppressed and that this suppression is mediated by passively acquired maternal antibodies [ 30–36]. However, this suppression is transient in nature and affects apparently mainly the antibody response [ 31, 33, 37], while for instance the generation of delayed type hypersensitivity (DTH) effector cells and memory cells is not impaired, thus enabling normal secondary responses [ 38].…”
Section: Maternal Immunization Confers More Than Passive Protection Onlymentioning
confidence: 99%
“…Since the 1940s until present, it has been reported that antibody responses at an early age in the offspring of immunized mothers are suppressed and that this suppression is mediated by passively acquired maternal antibodies [ 30–36]. However, this suppression is transient in nature and affects apparently mainly the antibody response [ 31, 33, 37], while for instance the generation of delayed type hypersensitivity (DTH) effector cells and memory cells is not impaired, thus enabling normal secondary responses [ 38]. Consequently, this misleading suppression mediated by the maternal antibodies can be overcome by a second immunization [ 39] or by increasing the antigen dose of the primary vaccination [ 40].…”
Section: Maternal Immunization Confers More Than Passive Protection Onlymentioning
confidence: 99%
“…In the fishery test, the serum physiological and biochemical indexes of fish can reflect the permeability of tissue cells, metabolism and immune function to some extent (Caruso et al, 2005). Erythrocytes are immune and participate in the immune regulation of the body and contain a variety of immune‐related substances (Muscoplat et al, 1977). Leucocytes play an important role in phagocytosis of foreign bodies, antibody production, resistance to pathogenic invasion and immunity (Muscoplat et al, 1977).…”
Section: Discussionmentioning
confidence: 99%